Gamma-ray emission from selected Wolf-Rayet binaries - Benaglia, Paula (2003)
In the colliding wind region of early-type binaries, electrons can be accelerated up to relativistic energies, as demonstrated by the detection of non-thermal radio emission from several WR+OB systems. The particle acceleration region is exposed to strong photon fields, and inverse-Compton cooling of the electrons could result in a substantial high-energy non-thermal flux. We present here preliminary results of a study of the binaries WR 140, WR 146, and WR 147 in the light of recent radio and ã-ray observations. We show that under reasonable assumptions WR 140 can produce the ã-ray flux from the GRO-EGRET source 3EG J 2022+4317. WR 146 and WR 147 are below the detection threshold.